BRAF-mutated colorectal adenocarcinomas: Pathological heterogeneity and clinical implications. (April 2022) - Angerilli, Valentina; Sabella, Giovanna; Centonze, Giovanni; Lonardi, Sara; Bergamo, Francesca; Mangogna, Alessandro; Pietrantonio, Filippo; Fassan, Matteo; Milione, Massimo
Abstract: Advances in molecular biology have markedly increased our understanding of the heterogeneous molecular landscape of colorectal cancer (CRC). Up to 15% of CRCs harbor the BRAF p.V600E somatic mutation ( BRAF mt), a well-established negative prognostic marker in patients with metastatic CRC (mCRC). The BEACON CRC trial set a new standard of care in patients with progressive BRAF mt cancers, consisting of the combination of encorafenib and cetuximab. On these bases, BRAF mutational testing is now recommended in patients with mCRC. However, efforts are needed to further stratify patients carrying this mutation. Here, we discuss the heterogeneous pathologic and molecular landscape of BRAF mt CRCs, focusing on the promises and pitfalls of molecular diagnostics, on novel biomarkers to improve patients' stratification and on the current diagnostic scenario for CRC. We believe that a better stratification based on histopathological features and novel molecular biomarkers should be performed to optimize patient management and therapeutic decision-making. Graphical Abstract: ga1 Highlights: BRAF mt is a negative prognostic marker in CRC. BRAF mt patients often do not respond to single tyrosine kinase inhibitors therapeutic regimens. It is fundamental to improve BRAF mt testing to define a proper therapeutic strategy. Promises and pitfalls of molecular diagnostics and novel biomarkers to improve BRAF mt CRC patients' stratification are discussed, along with the current diagnostic scenario. More efforts are needed to add knowledge for rational use of targeted and combined therapies.